Personality traits bias the perceived quality of sonic environments - Lindborg, PerMagnus (2018)
There have been few empirical investigations of how individual differences influence the perception of the sonic environment. The present study included the Big Five traits and noise sensitivity as personality factors in two listening experiments (n = 43, n = 45). Recordings of urban and restaurant soundscapes that had been selected based on their type were rated for Pleasantness and Eventfulness using the Swedish Soundscape Quality Protocol. Multivariate multiple regression analysis showed that ratings depended on the type and loudness of both kinds of sonic environments and that the personality factors made a small yet significant contribution. Univariate models explained 48% (cross-validated adjusted R2) of the variation in Pleasantness ratings of urban soundscapes, and 35% of Eventfulness. For restaurant soundscapes the percentages explained were 22% and 21%, respectively. Emotional stability and noise sensitivity were notable predictors whose contribution to explaining the variation in quality ratings was between one-tenth and nearly half of the soundscape indicators, as measured by squared semipartial correlation. Further analysis revealed that 36% of noise sensitivity could be predicted by broad personality dimensions, replicating previous research. Our study lends empirical support to the hypothesis that personality traits have a significant though comparatively small influence on the perceived quality of sonic environments.